Interest Rates and Government Debt : Are the Linkages Global Rather Than National? - Lutz, Mark (IMF Working Papers; Working Paper, 1991)
Given the increasing integration of financial markets, a better understanding of the effects of fiscal deficits and debt on real interest rates might be obtained by taking a global, rather than a national, perspective. The paper constructs aggregate flow and stock data (including GDP, fiscal deficits, government debt, and saving rates) and examines the empirical evidence of the global effect of fiscal policies on interest rates. The sensitivity of the results to the choice of deficit (central or general government), public debt (gross or net), and saving (gross or net), as well as the level and method of aggregation, is also examined.